SOSIALISASI DAN PENERAPAN BUDAYA K3 PADA PROYEK FIBER TO THE HOME (FTTH) DI PERUSAHAAN INTERNET SERVICE PROVIDER - Afiatna, Fatma Ayu Nuning Farida; Nur Muflihah; Titin Sundari; Sumarsono; Terdy Kistofer; Andhika Mayasari; Minto (ABIDUMASY, 2025)
The development of Fiber To The Home (FTTH) networks in the telecommunications sector carries significant occupational safety and health (OSH) risks due to field activities and the use of technical equipment. This community service aims to promote and implement an OSH culture in the FTTH project of PT. Garuda Media Telematika in Jombang Regency, East Java. To assess the effectiveness of the awareness program, qualitative descriptive analysis was employed through semi-structured interviews, participatory observation, and document analysis. The results indicate that worker participation in OSH awareness sessions reached 90.91%, with full compliance in using helmets and safety vests but lower adherence to wearing gloves (75%) and safety shoes (87.5%). Field observations revealed that OSH practices are in the moderate-to-good category, with main challenges including limited involvement of contract technicians, availability of certain personal protective equipment (PPE), and project target pressures. Management commitment, the existence of standard operating procedures (SOPs), and the role of supervisors were identified as key supporting factors, while technicians’ perception of OSH importance still requires improvement. These findings highlight the need for onboarding training, provision of ergonomic PPE, and strengthening the OSH culture through supervision and exemplary leadership. Implementing these recommendations is expected to enhance workplace safety and ensure the sustainable quality of FTTH projects.